Obesity and breast cancer - Mazur-Roszak, Małgorzata; Litwiniuk, Maria; Grodecka-Gazdecka, Sylwia (Contemporary Oncology/Współczesna Onkologia, 2010)
Obesity is described as pathological enlargement of adipose tissue. It causes metabolic disorders and organ failure and increases risk of many kinds of cancers. BMI > 25 mg/m 2 and low physical activity are associated with breast cancer pathogenesis. Insulin represents a major link between obesity and breast cancer; it not only participates in metabolic changes, but is also a well known mitogen. Adipocytes secrete leptin and adiponectin, which are important risk factors for breast cancer. Obese women show high leptin and low adiponectin levels. Decreased adiponectin level correlates with breast cancer risk. Obese patients tend to have non-palpable tumours, that can delay breast cancer diagnosis and worsen treatment prognosis. Therefore it is necessary to educate patients how to change their lifestyle, including adequate physical activity and diet.